(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
In the article, the negative impact of migration processes in the life of the society, its social and economic aspects, as well as recommendations for the prevention of social problems are given. Also, as a result of the increase in the volume of labor migration, the opportunities aimed at forming a mechanism of positive influence on the country’s economy and its implementation are highlighted. At this point, the study focuses on the problems of adaptation of migrants to a foreign environment and the negative consequences such as the assimilation formed in them as a result of this, as well as the formation of a marginal character. Scientific proposals aimed at preventing them are presented.